(untitled) (Revista de Estudios Brasileños, 2017)
Although the III International Pan-American Conference held in Rio de Janeiro in 1906 represented an important milestone for the relations between Brazil and the United States, it remains greatly understudied. The aim of this paper is to help overcome that. In order to achieve this aim, the text is divided into three parts. Firstly, I present the lead up of the Conference, describing the main results of the previous events and showing how they impacted the agenda making for Rio. Secondly, I briefly describe the atmosphere in Brazil, focusing on the ongoing debate on the relations with the United States and Pan-Americanism. The different perspectives of important men in policy and decision making regarding Foreign Affairs, such as the Baron of Rio Branco, Joaquim Nabuco and Oliveira Lima, are highlighted. Finally, both the symbolic meaning and the practical results of the Conference for inter-American relations in general and Brazil-US relations in particular are analyzed.